A Fast Scheduling Method for Massive Oblique Photography 3D Models. (30th August 2022) - Chen, Ruibo; Qu, Ruichao; Chen, Jiaxing; Lei, Jiangtao; Luo, Yitan; Liu, Rundong; Ma, Zhanyu
Abstract : In view of the large amount of oblique photography 3D model data and the fact that high-performance hardware devices cannot load and render massive oblique photography 3D models at one time, this paper provides a fast scheduling method for massive oblique photography 3D models: get the tile radius, side length, scheduling range, and other parameters from the original data, normalize the original tile to a hundred grid, use a regular grid + quadtree + hexadecimal tree to build a tile spatial index, resample the tile data at each level to generate the elevation model DEM and the real radiographic image TDOM, and use the DEM+TDOM method to reconstruct the layered and block top-level 3D model to achieve rapid scheduling and rendering of massive oblique photography 3D models. Experiments show that the method is efficient and feasible and can meet the visualization and real-time interaction requirements of massive urban 3D models.